Decrease in Attentional Performance After Repeated Bouts of High Intensity Exercise in Association-Football Referees and Assistant Referees - Schmidt, Sergio L.; Schmidt, Guilherme J.; Padilla, Catarina S.; Simões, Eunice N.; Tolentino, Julio C.; Barroso, Paulo R.; Narciso, Jorge H.; Godoy, Erik S.; Costa Filho, Rubens L. (Frontiers in Psychology, 2019)
Referees and assistant referees are submitted to high physical stress during matches. Pressure to make decisions in front of large crowds is another potential stressor. These two stressors can impair attention executive control, depending on physical fitness and individ-ual vulnerability or resilience to situational pressure. Error percentage for referees and as-sistants may reach around 14% during a soccer match. Although previous studies have suggested that soccer referees and assistants should take cognitive assessments, they are only required by Fédération Internationale de Football Association (FIFA) to demonstrate knowledge of the rules and pass annually in a fitness test (FIFA-Test). This study aimed to assess attention performance in referees and assistants before and after the mandatory FIFA-Test. It is hypothesized that the high physical demands associated with the pressure to pass the FIFA-Test would interfere with attention performance. The sample included 33 referees and 20 assistants. The continuous visual attention test (CVAT) consisted of a 15-minute Go/No-go task. Performance in the CVAT is based on four variables: omission and commission errors, reaction time, and variability of reaction time (VRT). Failure in the CVAT was defined by a performance below the 5th percentile of the age-and sex matched normative data in at least one variable of the CVAT. Before the FIFA-Test all participants performed the CVAT. The second CVAT began 3 to 7 minutes directly following comple-tion of the FIFA-test. Considering only the officials who passed both the FIFA-Test and the first CVAT (19 referees,15 assistants), 44% (9 referees and 6 assistants) exhibited a performance decline in the second CVAT. A significant increase in VRT was found after the high intensity exercise. As increase in VRT is thought to reflect executive dysfunctions and lapses of attention, we concluded that physical fitness alone may not be enough to help officials cope with the physical and contextual stresses associated with the FIFA-Test. These data suggest that over 35% of soccer referees and their assistants who were consid-ered physically able to referee matches may not be mentally prepared for the attentional de-mands of refereeing soccer matches.